2014
DOI: 10.1093/hmg/ddu148
|View full text |Cite
|
Sign up to set email alerts
|

Activating mutations in RRAS underlie a phenotype within the RASopathy spectrum and contribute to leukaemogenesis

Abstract: RASopathies, a family of disorders characterized by cardiac defects, defective growth, facial dysmorphism, variable cognitive deficits and predisposition to certain malignancies, are caused by constitutional dysregulation of RAS signalling predominantly through the RAF/MEK/ERK (MAPK) cascade. We report on two germline mutations (p.Gly39dup and p.Val55Met) in RRAS, a gene encoding a small monomeric GTPase controlling cell adhesion, spreading and migration, underlying a rare (2 subjects among 504 individuals ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 68 publications
3
84
0
Order By: Relevance
“…Mutations at that RRAS G39 promote enhanced serum-dependent MEK, ERK, and AKT phosphorylation in vitro. 30 We identified mutations in several genes (eg, PAK3, USP6, ABCF1, STK39) that were uncommon but may confer important effects within individual PTNFLs. Further study is needed to determine the contribution of these mutations within cases of PTNFL.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations at that RRAS G39 promote enhanced serum-dependent MEK, ERK, and AKT phosphorylation in vitro. 30 We identified mutations in several genes (eg, PAK3, USP6, ABCF1, STK39) that were uncommon but may confer important effects within individual PTNFLs. Further study is needed to determine the contribution of these mutations within cases of PTNFL.…”
Section: Discussionmentioning
confidence: 99%
“…Less frequently, these patients develop severe MPD, juvenile myelomonocytic leukemia (JMML), or other forms of leukemia (2,5). NS is inherited in an autosomal dominant manner and results from germ-line mutations in at least 11 different genes including Protein Tyrosine Phosphatase Non-Receptor type 11 (PTPN11), Son of Sevenless homolog 1 (SOS1), KRAS, NRAS, RAF1, BRAF, MEK1, SHOC2, CBL, RIT1, and RRAS, most of which are involved in mediating RAS signaling (3,(6)(7)(8). Among these loci, PTPN11 is the most frequently mutated, in about 50% of NS patients.…”
mentioning
confidence: 99%
“…Indeed, we have recently shown that RRAS, another RAS-like GTPase, is mutated in rare cases of NS and in some cases of JMML. 9 Similar to classic Ras and R-Ras, Rit proteins have been shown to display oncogenic properties, and GTPasedeficient variants cause growth transformation in NIH 3T3 mouse fibroblasts. 30 The expression of wild-type or oncogenic RIT1 in PC6 cells induces in most cases both the phosphorylation of ERK via MEK activation and a robust activation of PI3K/AKT signaling.…”
Section: Rit1-related Noonan Syndrome H Cavé Et Almentioning
confidence: 99%